PERILAKU TIDAK MEMILIH DALAM PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA TANJUNGPINANG TAHUN 2018 DI KELURAHAN TANJUNGPINANG KOTA KECAMATAN TANJUNGPINANG KOTA - Kevin K; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The characteristic of a democratic country is how much the state engages the community in planning and carrying out general elections because political participation of the community (voters) is an important aspect in a democratic state order, there is a phenomenon in the Tanjungpinang Kota Kelurahan, namely the level of participation or the percentage of pilkada from the Riau Islands KPU recapitulation data there is a low level of participation in tanjung pinang urban village that is only 41.95% considering tanjung pinang urban village is an urban community area that has a high level of education with prosperous employment status should be able to provide higher political participation results but vice versaIn this study there are two main concepts, namely; voting behavior and non-voting behavior that divides four factors, namely Socio-Economic Factors, Psychological Factors, Rational and Structural Factors as a result of research that the author has done in the graduation of Tanjung Pinang, Tanjung Pinang Subdistricts, by spreading koesioner in 100 respondents.Causes of Tanjungpinang Urban Village Community Not Voting in the Election of Mayor and Deputy Mayor of Tanjungpinang 2018 there are several main causes, namely voters domiciled outside the area, then the theory of non-voting or non-voting behavior theory is the rationalist and psychological factors which are the main factors of the community not voting in election of mayor and deputy mayor of Tanjumgpinang in 2018 in Tanjungpinang Kota Sub-District, Tanjungpinang Kota Sub-District. Keywords: Non-voting behavior, political participation.